تركيب الإضافة في سورة الدخان ومعانيها - Rachmad Akbar Alimurrochim (UIN Fatmawati Sukarno Bengkulu, 2021)
The purpose of writing this scientific paper is to discuss in detail about genetive (al-idhafah) and its meanings contained in the Qur’an, more specifically in Surah al-Dukhan. With the hope that we can understand further about the purpose of Allah's commands and prohibitions contained in the holy Qur’an and understand and be aware of the warnings and severe threats to those who do not accept what is presented by the holy book of the Qur’an in the form of blessings and graces that are addressed to them all creatures. The research method used in compiling this scientific work is a qualitative method, namely by analyzing genetive (al-idafah) based on the existing theory of linguistics (Nahw) and then describing its implementation which is found in the verses of the Qur’an. Regarding the discovery of genetive (al-idafah) in the letter al-Dukhan in this writing, sometimes 1, 2 to 3 forms of genetive (al-idafah) are found in one verse. Meanwhile, the meaning contained in the arrangement of genetive (al-idafah) in the letter al-Dukhan was found to be various, including al-idafah al-Lamiyyah, al-idafah al-Baya niyyah, al-idafah al-zarfiyyah, and al-idafah al-tashbihiyyah.